1993
DOI: 10.1200/jco.1993.11.4.783
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of women at risk for psychosocial distress in the year after breast cancer.

Abstract: The detailed listing of problems provided by the CARES may be helpful to clinicians in their interactions with patients. The need for preventive and early intervention for the at-risk patients is underscored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
132
1
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(142 citation statements)
references
References 29 publications
4
132
1
5
Order By: Relevance
“…In addition to global QOL, assessment of emotional functioning shows low levels at baseline too, with no significant changes during follow-up in both groups. An explanation for low levels at baseline is that patients being informed about the breast cancer diagnosis before surgery induced psychological distress (Fallowfield et al, 1986;Ganz et al, 1992;Coscarelli Schag et al, 1993). In this study the Karnofsky performance status score was, for most patients, over 90 at baseline and showed no differences in patients' physical condition in both groups during follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to global QOL, assessment of emotional functioning shows low levels at baseline too, with no significant changes during follow-up in both groups. An explanation for low levels at baseline is that patients being informed about the breast cancer diagnosis before surgery induced psychological distress (Fallowfield et al, 1986;Ganz et al, 1992;Coscarelli Schag et al, 1993). In this study the Karnofsky performance status score was, for most patients, over 90 at baseline and showed no differences in patients' physical condition in both groups during follow-up.…”
Section: Discussionmentioning
confidence: 55%
“…Some data suggest that the onset of mood disorders may vary according to the stage of cancer treatment, 20,31 staging 32 or type of treatment 33,34 while others found no cancer-specific influence. 12,15,16 Breast cancer and depression are public health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not investigate risk factors within the cohort, other studies have identified clear risk factors for depression and anxiety among cancer patients. Such risk factors tend to be more closely related to the patient than factors surrounding disease or treatment and include lack of an intimate confiding relationship, marital issues, and history of depression or previous psychological treatment [1,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%